2005
DOI: 10.1007/s10734-004-6363-z
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ beliefs and intentions concerning teaching in higher education

Abstract: A questionnaire measuring nine different aspects of teachers' beliefs and intentions concerning teaching in higher education was distributed to teachers at four institutions in the United Kingdom, yielding 638 complete sets of responses. There was a high degree of overlap between the participants' scores on the subscales measuring beliefs and intentions, and analyses of both sets of scores yielded two factors reflecting an orientation towards learning facilitation and an orientation towards knowledge transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
199
2
23

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(244 citation statements)
references
References 57 publications
11
199
2
23
Order By: Relevance
“…Les conceptions vont de la reproduction, où l'enseignement est perçu comme une transmission des connaissances, à la transformation, où l'enseignement est vu comme un encouragement aux changements tant cognitifs qu'affectifs chez les apprenants. Puisqu'il y a peu de données probantes suggérant que seule l'expérience d'enseignement permet l'adoption du concept de transformation [59] , il devient impératif que les établis-sements investissent et soutiennent leur corps enseignant en transformant leurs conceptions, ce qui devrait, par ricochet, améliorer leur approche pédago-gique. Pour les individus qui choisissent une carrière d'enseignement, ce développement professionnel peut progresser jusqu'à sa conclusion logique : d'enseignant à enseignant expert, puis à expert en éducation [60,61] ou peut-être leader pédagogique [8,34,61,62] .…”
Section: Préparation à L'enseignementunclassified
See 2 more Smart Citations
“…Les conceptions vont de la reproduction, où l'enseignement est perçu comme une transmission des connaissances, à la transformation, où l'enseignement est vu comme un encouragement aux changements tant cognitifs qu'affectifs chez les apprenants. Puisqu'il y a peu de données probantes suggérant que seule l'expérience d'enseignement permet l'adoption du concept de transformation [59] , il devient impératif que les établis-sements investissent et soutiennent leur corps enseignant en transformant leurs conceptions, ce qui devrait, par ricochet, améliorer leur approche pédago-gique. Pour les individus qui choisissent une carrière d'enseignement, ce développement professionnel peut progresser jusqu'à sa conclusion logique : d'enseignant à enseignant expert, puis à expert en éducation [60,61] ou peut-être leader pédagogique [8,34,61,62] .…”
Section: Préparation à L'enseignementunclassified
“…Plusieurs facteurs situationnels ou liés au contexte (par exemple : le leadership, une reconnaissance appropriée), au sein de l'établissement ou de différentes disciplines, peuvent contribuer à des discordances, incluant la valeur accordée à l'enseignement [58,59,88,99] . Ces facteurs peuvent aussi avoir des conséquences sur l'engagement et l'allocation des ressources de l'établissement et, ainsi, sur sa participation dans le développement professoral [5,66,90] .…”
Section: Le Manque De Soutien Institutionnel Du Développement Professunclassified
See 1 more Smart Citation
“…The study undertaken had focused on how transformative learning could be facilitated in specific educational situation for specific learners. In a study, Norton et al (2005) found no differences in teaching attitude and intent between teachers who had joined training programs and teachers who had no attended training. However, positive results of the effectiveness of teacher trainings have also been presented.…”
mentioning
confidence: 93%
“…These are the teachers who introduce new reforms in society. Teacher is the key component of education system (Norton et al, 2005).…”
mentioning
confidence: 99%